From Children's Giftedness to Real Talent: The Problem of "Transition" - Yurkevich, V.S. (Sovremennaâ Zarubežnaâ Psihologiâ, 2021)
The main problem of gifted children is the "transition" of their increased intellectual capabilities into talent, as the basis of creative activity, or, in another formulation, the transformation of children's giftedness into an actual talent. Analysis of available materials shows that the cognitive need of a significant part of these children takes the character of passive accumulation of a large amount of knowledge and therefore becomes an obstacle to such a transition. The search need is considered to be a basic factor, which is the "engine" of the creative realization of a gifted person, which ensures the search for new solutions and ways of action in contradictory and uncertain situations for the subject, and, thus, becomes the basis of his talent, future creative achievements. It is shown that in a number of gifted children and, above all, in the so-called "prodigies" the need for search is early and very significantly deformed, which in most cases is directly related to social influences. The article deals with the causes and consequences of a significant deformation of the search need in gifted children. Главной проблемой одаренных детей является «переход» их повышенных интеллектуальных возможностей в талант, как основе творческой деятельности, или, в другой формулировке, превращение детской одаренности в актуальный талант. Анализ имеющихся материалов показывает, что познавательная потребность у значительной части этих детей принимает характер пассивного накопления большого объема знаний и потому становится препятствием для такого перехода. В качестве базового фактора, который является «мотором» творческой реализации одаренного человека, рассматривается поисковая потребность, которая обеспечивает поиск новых решений и способов действия в противоречивой и неопределенной для субъекта ситуации, и, таким образом, становится основой его таланта, будущих творческих достижений. Показано, что у ряда одаренных детей и прежде всего у так называемых «вундеркиндов» потребность в поиске рано и весьма существенно деформируется, что в большинстве случаев прямо связано с влиянием социума. В статье рассматриваются причины и следствия значительной деформации поисковой потребности у одаренных детей.